Evaluation of nutritional status and factors contributing to malnutrition in children aged 6 to 59 months in the Luiza Health Zone, Democratic Republic of the Congo - MUANDA Gustave MUALA; MUTOKE Louis MBUAMBUA; NTAMBUE Alfred DIKEBELA; KATENDE Pascal KATALAYI; MUKUMBULE Rose NGALULA; NDUMBI Antoine LUNGENYI; LUENDU André KABEYA; NTONDELE Herman LUYINU; KANGOYANGALA Nicolas KINAMBOLI (Orapuh Journal, 2025)
Introduction